Analisis Penerapan Game Wordwall Dalam Pembelajaran IPAS Materi Gaya di sekitar kita Di Sekolah Dasar - Rosani, Talitha Fadhilah; Heryadi, Yadi; Widiyawati, Wiwin; Yunanto, Rio Putra (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the application of Wordwall educational games as a learning medium in increasing students' understanding and involvement in the material. The method used is qualitative descriptive with a case study approach in one of the elementary schools, involving observation, interviews, and documentation as data collection techniques. Participants consisted of one teacher and 25 students of grade IV. The results of the study show that the use of Wordwall is able to significantly increase the understanding of style concepts, strengthen students' active involvement in the learning process, and foster higher learning motivation. This medium helps bridge abstract concepts into more concrete and enjoyable experiences, in accordance with the principles of constructivistic learning. However, there are challenges such as the limitations of technological devices and the need to develop teachers' competencies in managing digital game-based learning. This research reinforces the importance of integrating technology in basic learning to create an effective and enjoyable learning process. In conclusion, the application of the Wordwall game is a relevant and potential learning strategy for the Style material around us in elementary school students, which supports the achievement of optimal student understanding and engagement.